The Environmental Education Dimensions for Sustainable Development - IOVAN, Marțian (Journal of Legal Studies, 2015)
Based both on a historical approach regarding the evolution of the environmental education between 1960 and present days, and on empirical research as well, the author proves that the efficiency of the environmental education could be much higher if included within the broader sphere of moral and civic education and if it is driven by a more extensive ideal sprung from the fundamental human right to a clean and well preserved environment, by the contemporary moral and civil values. The author pleads and motivates for an increased capitalization of the humanities and social sciences, of art, of environmental ethics and aesthetics in shaping "the ecological personality" of the tomorrow people. When shaping these personality traits through environmental education activities, one must emphasize the importance of practice and applied actions aimed to protect the environment, and in general, the practice of civic-moral education methods.